Airway inflammation in patients with chronic non-asthmatic cough. Issue 2 (23rd October 2012) - Grabowski, Marcin; Seys, Sven; Decraene, Ann; Kasran, Ahmad; Dilissen, Ellen; Barg, Wojciech; Medrala, Wojciech; Dupont, Lieven J; Panaszek, Bernard; Bullens, Dominique M A
Abstract : Introduction: Chronic non-asthmatic cough (CC) is a clinical challenge and underlying pathophysiological mechanisms remain still not completely understood. One of the most common comorbidities in CC is gastro-oesophageal reflux disease (GORD). Airway epithelium damage can contribute to airway inflammation in CC. Aims: We studied airway inflammation in patients with CC compared to healthy controls. Patients with GORD were treated with proton pump inhibitors (PPI) and cough response to PPI was evaluated. Patients and methods: Sputum was induced in 41 adults with CC and 20 healthy non-smokers who were age and sex matched. We compared sputum differential cell count by cytospin and cytokine and chemokine production at the mRNA and/or protein levels by real-time (RT)-PCR and cytokine bead array (CBA), between patients with CC and healthy subjects. Furthermore we studied airway inflammation in patients with different comorbidities. Results: No differences in sputum differential cell counts were observed between patients with CC and healthy subjects. Sputum monocyte chemoattractant protein-1 (MCP-1) protein levels were significantly higher in patients when compared to controls. Thymic stromal lymphopoietin (TSLP) mRNA was significantly more often expressed in sputum of patients with CC than from healthy controls. Sputum transforming growth factor (TGF)-β levels did not differ between patients and controls, but were significantly lower in the PPI responders compared to the non-responders; p=0.047. There is no evidence for impaired T helper cell (Th)1/Th2/Th17 balance in CC. Patients with reflux oesophagitis (RO) have significantly more sputum eosinophils than patients without RO. Conclusions: CC is a condition presenting with different disease phenotypes. High sputum MCP-1 levels are present in a large group of patients with CC and a majority of these patients with CC have increased sputum TSLP levels, most likely produced by damaged airway epithelial cells.